Pete the cat and the missing cupcakes - Dean, James. 1969-; Dean, James, 1957- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
Pete the Cat and his friends bake cupcakes for a party, but the cupcakes go missing.
School Library Journal
School Library Journal, November 2016
1.4
K-3
K-3
English
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Pete, -- the Cat (Fictitious character) -- Fiction; Pete, -- the Cat (Fictitious character) -- Fiction; Cats -- Juvenile fiction; Cupcakes -- Juvenile fiction; Friendship -- Juvenile fiction; Cats -- Fiction; Cupcakes -- Fiction; Friendship -- Fiction; Cats -- Fiction; Cupcakes -- Fiction; Friendship -- Fiction